Modern aspects of foreign trade policy of the Russian Federation and its export potential in the grain market - E. V. Nagovitsyna; D. S. Tusin (Вестник университета, 2023)
The article assesses the importance of the Russian Federation for global agricultural markets, describes relevant risks associated with the conflict in Ukraine and proposes ways to address the challenges of exporting Russian products to international markets in order to prevent famine and social problems in the world. The study includes an overview of Russian and foreign specialised literature, which allowed to systematize the ways to achieve the goal set that had already been proposed and develop new ones. Logical, economic and statistical methods as well as the methods of synthesis, system and SWOT analysis served as a basis for the study. Using the methods of theoretical analysis, the authors identified specific features of the Russian and global markets’ advancement. Economic and statistical methods provided an opportunity to describe trends and factors that determine the direction of the grain market’s development. Fundamental food security problems as well risks associated with the dependency of various states on the imports of feed and fertilizers from Ukraine and the Russian Federation were examined. A conclusion according to which the ambiguous geopolitical situation can hinder food exporting to many countries was made. The importance of restructuring the logistics system of grain supplies at the current stage was proved, and measures aimed at countering critical challenges of and threats to exporting agricultural products from the Russian Federation were proposed.